Woody Species Composition, Structure, Regeneration Status and Carbon Storage of Mkulazi Forest Reserve in Tanzania - Mwakalukwa, Ezekiel E.; John, Christoganus; Lyimo, Paulo J. (Tanzania Journal of Science, 2024)
Little is known about the status of forest condition and carbon storage potential of Mkulazi forest reserve (MFR) located in Morogoro District, Tanzania. This study was conducted to assess i) woody species composition, richness and diversity, ii) stand structure, iii) regeneration status and iv) carbon storage. Data collection for vegetation involved establishment of 100 concentric circular sample plots in the forest area of 65,710 ha. A total of 54 plant species for trees and shrubs with DBH ≥ 5 cm that belongs to 20 plant families were identified. The diversity of woody species was high (H’ = 3.11), while Stem density was 336 ± 126 stems ha-1, basal area was 9.48 ± 2.88 m2ha-1 and stand volume was 96.22 ± 32.51 m3ha-1. For the regeneration with DBH < 5 cm, a total of 26 plant species belonging to 11 plant families were identified. The diversity of woody species was also high (H’ = 3.14) and stem density was 1,198 ± 847 stems ha-1. The mean carbon stocks above ground for trees and shrubs with DBH ≥ 5 cm were 32.13 ± 10.91 Mg C ha-1 and that of below ground were 11.84 ± 3.58 Mg C ha-1. The observed high diversity of woody species, regeneration status and relatively high carbon storage potential signifies the importance of continuing protecting this reserve.